Fixation of a human rib by an intramedullary telescoping splint anchored by bone cement - Liovic, P.; Sutalo, Ilija; Marasco, S. (Taylor & Francis, 2016)
A novel concept for rib fixation is presented that involves the use of a bioresorbable polymer intramedullary telescoping splint. Bone cement is used to anchor each end of the splint inside the medullary canal on each side of the fracture site. In this manner, rib fixation is achieved without fixation device protrusion from the rib, making the splint completely intramedullary. Finite element analysis is used to demonstrate that such a splint/cement composite can preserve rib fixation subjected to cough-intensity force loadings. Computational fluid dynamics and porcine rib experiments were used to study the anchor formation process required to complete the fixation.